The effect of gamma ray on agronomic characters of rice (oryza sativa) / Nurul Hanani Kamarudin - Kamarudin, Nurul Hanani (2016)
Plant mutagenesis by ionizing radiation specifically gamma ray are widely applied to develop better mutant varieties in rice. Thus, the aim of this study was to determine the effect of gamma radiation towards agronomic characters. Seven doses of gamma ray (50,100,200,300,400,500, and 600Gy) were applied to both seeds of Bertih and Hila to determine the lethal dose (LDso). Results showed that LD50 for Bertih and Hila were between 255 and 345Gy respectively. Correlation study demonstrated that there was a positive relation between dose of gamma ray and agronomic characters. Hila gave negative results for the correlation study. This study provides fundamental findings for agriculturalists to develop local mutant variations in future.